Clinical laboratory follow-up of workers who suffered accidents with biological material in hospital institutions - Mariana Guimarães Cardoso; Danielli Rafaeli Candido Pedro; Raquel Gvozd Costa; Paloma de Souza Cavalcante Pissinati; Mariana Ângela Rossaneis; Maria do Carmo Fernandez Lourenço Haddad (Universidade Federal de Santa Maria, 2019)
Objective: To analyze the clinical laboratory follow-up of workers who suffered accidents with biological material in hospitals (AWBM). Method: cross-sectional, quantitative study with analysis of medical records of 550 workers who suffered AWBM in the area of the 17th Regional Health of the State of Paraná, from October 2010 to December 2013. For the analysis of the association the ratio of prevalence was used (RP), and Wald's chi-square test to determine if there were differences between study variables and abandonment of clinical follow-up. Results: 51.5% of those affected did not give clinical follow-up to the care recommended by the Ministry of Health's AWBM protocol. There was greater abandonment of treatment when there was no patient. Conclusions: More than half of the injured people did not continue the clinical follow-up, highlighting the importance of strategies for worker health.